A Needs Analysis of Basic Reading Instruction for University-Level EFL Students - Nemo, Maximus Leonardus; Rinantanti, Yulini; Wabiser, Yan Dirk; Kobepa, Niko; Sobolim, Amelia D.; Daud, Enikartini Binti (JOLLT Journal of Languages and Language Teaching, 2025)
Essential for EFL students are basic reading skills, including letter recognition, word decoding, and comprehension of phrases. Learners struggle with more difficult materials and participate actively in class discussions without honing these abilities. This study aims to investigate EFL students’ needs analysis of basic reading instruction. This descriptive qualitative research design was used with the 2nd semester students of the English Language Education Study Program of Universitas Cenderawasih as the subjects of this research, using in-depth interviews and non-participant observation as data collection tools, and having 19 students as the respondents. Based on the interviews with 19 EFL students, most of them find textbook-based reading materials repetitious and devoid of visual aids, with culture, education, health, and sport. They were interesting, relevant materials that they enjoyed more. Particularly in science and academic writing, students find difficulty with longer passages, foreign vocabulary, and challenging books. They said they prefer digital resources to help understanding, including interactive exercises, audiobooks, and vocabulary lists. These findings underline the importance of level-appropriate, interesting reading materials as well as the usage of multimedia tools to assist different learning requirements. This study concludes that EFL students find challenges with standard, textbook-based reading materials, which emphasize the need for analysis for more relevant, interactive, and visually accompanied content to better fit their interests and improve reading comprehension and enthusiasm. The study recommends utilizing various reading materials, contextualized subjects, and needs-based scaffolding to improve engagement and understanding in curriculum development. EFL programmes can help learners improve their language skills.